Biodiversity and Multifunctional Features of Lactic Acid Bacteria Isolated From Table Olive Biofilms - Benítez-Cabello, Antonio; Calero-Delgado, Beatriz; Rodríguez-Gómez, Francisco; Garrido-Fernández, Antonio; Jiménez-Díaz, Rufino; Arroyo-López, Francisco Noé (Frontiers in Microbiology, 2019)
In the present study, a total of 554 lactic acid bacteria (LAB) isolates were obtained from the olive surface of Manzanilla, Gordal, and Aloreña cultivars processed as green Spanish-style or directly brined (natural) olives. The isolates obtained from industrial processes were genotyped by rep-PCR with primer GTG5, collecting a total of 79 different genotypes. The α-biodiversity indexes showed that the LAB diversity was higher in the biofilms on the fruits which followed the Spanish-style process than in those just brined. Sixteen genotypes had a frequency higher >1% and were identified, by multiplex PCR recA gene and 16S gene sequencing, as belonging to L. pentosus (n=13) and L. plantarum (n=3) species. A multivariate analysis based on a dataset with 89,744 cells, including technological (resistance to salt and pH, production of lactic acid, auto and co-aggregation with yeast species, β-glucosidase and esterase activities), and potential probiotic characteristics (survival to gastric and pancreatic digestions, resistance to antibiotics, inhibition of pathogens, presence of bsh genes, cholesterol removal, hemolytic, α-glucosidase, β-galactosidase, and phytase activities) showed that the 16 genotypes could be grouped into 3 great phenotypes. Thus, the genotype biodiversity in table olive biofilms was limited but, at phenotype level, it was even lower since L. pentosus predominated clearly (80.15% isolates). L. pentosus Lp13 was the genotype with the most promising characteristics for its use as a multifunctional starter, with this strain being and ubiquitous microorganism present in both natural and lye-treated olive fermentations.